An autopsy report of a familial amyotrophic lateral sclerosis case carrying VCP Arg487His mutation with a unique TDP‐43 proteinopathy. Issue 2 (7th January 2021) - Matsubara, Tomoyasu; Izumi, Yuishin; Oda, Masaya; Takahashi, Masatoshi; Maruyama, Hirofumi; Miyamoto, Ryosuke; Watanabe, Chigusa; Tachiyama, Yoshiro; Morino, Hiroyuki; Kawakami, Hideshi; Saito, Yuko; Murayama, Shigeo
Abstract : We here report an autopsy case of familial amyotrophic lateral sclerosis (ALS) with p.Arg487His mutation in the valosin‐containing protein (VCP) gene ( VCP ), in which upper motor neurons (UMNs) were predominantly involved. Moreover, our patient developed symptoms of frontotemporal dementia later in life and pathologically exhibited numerous phosphorylated transactivation response DNA‐binding protein of 43 kDa (p‐TDP‐43)‐positive neuronal cytoplasmic inclusions and short dystrophic neurites with a few lentiform neuronal intranuclear inclusions, sharing the features of frontotemporal lobar degeneration with TDP‐43 pathology type A pattern. A review of previous reports of ALS with VCP mutations suggests that our case is unique in terms of its UMN‐predominant lesion pattern and distribution of p‐TDP‐43 pathology. Thus, this case report effectively expands the clinical and pathological phenotype of ALS in patients with a VCP mutation.